Investigating the carbon leakage effect on the environmental Kuznets curve using luminosity data - Arne Steinkraus (Technische Universität Braunschweig, Institut für Volkswirtschaftslehre, 2016)
This paper studies the effect of carbon leakage on the environmental Kuznets curve (EKC) using satellite nighttime light data. I show that nighttime lighting is an important variable for estimating carbon dioxide emissions that is superior to other existing indicators and covers all countries in the world. I find evidence of an inverted-U shaped relationship between light and, thus, greenhouse gas emissions and income, with a turning point at approximately US 50,000. However, the relationship is primarily driven by changes in the structure of international trade, implying strong carbon leakage effects. Consequently, environmental regulations that become operative in only one part of the world may fail without global coordination.
Keywords: F18; F64; Q50; 330; Environmental Kuznets Curve; Carbon Leakage; Nighttime Lighting